Employment Adjustments to Increased Imports: Evidence from a Developing Country - Beyza Ural Marchand (Institute of Labor Economics (IZA), 2025)
This paper examines the impact of imports from developed countries on industry-specific employment in India between 1983 and 2010. The identification strategy relies on comparing differential changes in import exposure across regions to the differential changes in employment within industries. The variation in the changes in imports to other developing countries is used to identify the component of the changes in imports driven by world demand. The results suggest that the increase in import exposure during the post-liberalization period reduced agricultural employment but increased employment in manufacturing, business, and social services. No significant impacts were found in the pre-liberalization period.
Keywords: F16; J21; J23; O33; 330; Imports; International Trade; Employment